Localization and Activity of Inflammatory Bowel Disease Using 111ln Leukocyte Imaging - Hotze, A.; Briele, B.; Wolf, F.; Biersack, H. J.; Knapp, F. F. (Nuklearmedizin - NuclearMedicine, 1988)
A prospective study was initiated to compare the clinically proven results concerning localization/extent and activity of inflammatory bowel diseases with those of 111ln-oxine leukocyte imaging. All patients studied were completely examined with barium enema x-ray, clinical and laboratory investigations, and endoscopy with histopathology. A total of 31 leukocyte scans were performed in 15 patients (12 with Crohn’s disease, 3 with ulcerative colitis). The scans were graded by comparing the cell uptake of a lesion (when present) and a bone marrow area providing a count ratio (CR). The inflammatory lesions were correctly localized on 26 leukocyte scans, and in 21 scans the scintigraphically estimated extent of disease was identical to endoscopy. In 5 cases the disease extent was underestimated, 4 scans in patients with relapse of Crohn’s disease were falsely negative, and in one patient with remission truly negative. The scintigraphically assessed disease activity was also in a good agreement with clinical disease activity based on histopathology in all cases. We conclude that leukocyte imaging provides valuable information about localization and activity of inflammatory bowel disease.